International prescribing patterns for mood illness: The international mood network (IMN) - Mauer, Sivan; Alahmari, Rami; Vöhringer, Paul; Vergne, Derick; Dalley, S; Ghaemi, S. Nassir; Lövdahl, Hans; Correa ُE; Patkar, A; Pae, Chi- Un; Strejilevich, Sergio (Journal of medical and pharmaceutical sciences, 2020)
Objective: The study aimed to uncover the feasibility of designing an international network that builds a common database for mood disorders, and to provide preliminary data for different treatment prescribing patterns around the world. Methodology: A research database was designed in partnership with physicians and researchers known to treat mood disorders, and the participating websites were asked to provide data for 10 to 50 people initially. This work was conducted under the auspices of a committee that includes representatives from North and South America, Europe and Asia, and data was collected from multiple sites using a central system on the Internet and then analyzed, and each of the participating sites obtained approval from the IRB (Institutional Review Board) For his participation in the International Mood Network, the Research Ethics Board of Tufts Medical Center approved and supervised the entire project. Research limitations: The study sample included more than half of the population from one country (the United States) with the possibility of cultural bias. Results: Of the 186 people who participated in the International Mood Disorder Network (IMN), most of them were given the following mood stabilizers: lithium (64%), lamotrigine (37%), valproate (31%), carbamazepine (3%), 79% diagnosed with a disorder Not Otherwise Specified (21), and 21% of them were diagnosed with major depressive disorder. 81% of people used antidepressants at some point. 25% were diagnosed with anti- depressive mania and 26% were diagnosed with rapid- fluctuating disorders related to antidepressants. The results also revealed that mood stabilizers are described more often in Europe (86%), antipsychotics in South America (70%), and antidepressants in Asia (58%). Conclusion: The results confirmed the diversity of the database of international mood disorders, and their enforceability (i.e. confirmed their feasibility), and some important regional differences were observed in describing psychological treatments for mood disorders, with increased use of mood stabilizers in Europe and South America, and increased use of antidepressants in Non- European population.